Genotyping of AR and PSA polymorphisms in a patient with Klinefelter syndrome, non-Hodgkin lymphoma, and adenocarcinoma of the prostate - dos Santos, R. M.; Rainho, C. A.; Trindade, JCS; de Camargo, JLV; Rogatto, Silvia Regina [UNESP] (Elsevier B.V., 2004)
It has been hypothesized that the AR (androgen receptor) gene binds the two PSA (prostate-specific antigen) alleles with differing affinities and may differentially influence prostate cancer risk. In this article, we report a case of adenocarcinoma of the prostate in a 56-year-old man with Klinefelter syndrome (47,XXY) and non-Hodgkin lymphoma, as well as the AR and PSA genotype. AR and PSA gene polymorphisms were analyzed by polymerase chain reaction-based methods using DNA from peripheral white blood cells and the prostate cancer. We determined the methylation status of the AR gene on the X chromosome. The patient presents with the AG genotype for the ARE-I (androgen response element) region of the PSA gene. We detect the presence of two short AR alleles with 19 and 11CAG repeats each. Unmethylated alleles were demonstrated for both. The shorter allele was inactive in more than 60% of total DNA in both control blood and prostate cancer cells. The presence of short AR alleles and the G allele of the PSA gene may contribute to the development of prostate cancer in a 47,XXY patient. (C) 2004 Elsevier B.V. All rights reserved.